PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI PADA MATERI SEL (MONOSEL) - Niki Desvidisa Aryani; Amelia Lestari; Ardina Dwi Inayah; Yunita Kurniasih (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2019)
Learning media in the form of games is able to provide a pleasant learning atmosphere for students. Therefore, a game-based learning media is needed. This study aimed to develop learning media on cell material. The type of research was research & development (R & D) using Borg and Gall design.. The trial was carried out for class X students of SMA 1 Bekasi. The research data was obtained from the product assessment questionnaire. The results of the media expert's research were 83%; material experts were 76.25%; small group trials were 83.5%; and large group trials were 83.5%. The overall assessment obtained an average percentage of 81.56% with a very decent interpretation.